KEMAMPUAN KEUANGAN DAERAH SEBAGAI ACUAN DALAM MEMBERIKAN TUNJANGAN BAGI ANGGOTA DPRD KABUPATEN SUBANG TAHUN 2022 - Rakhmat Haryono; Hendriady de Keizer; Wawan Hermawan; Marizca Amalia Putri (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2022)
Regional financial capacity is used as a baseline in the calculation of the amount of allowances for DPRD officers and members, especially in Subang Regency. Determination of the amount of regional financial capacity is influenced by the amount of regional general revenue and expenditure for state civil servants. In addition to receiving welfare benefits, the leadership and members of the Subang Regency DPRD based on PP No. 18 of 2017 also received housing and transportation allowances that did not exceed the allowances for the leadership and members of the West Java Provincial DPRD. The results of this study are used to identify the general picture, problems in implementing existing policies, and knowing the amount of housing and transportation allowances for the Leaders and Members of the Subang Regency DPRD.